(untitled) (Forum Agribisnis, 2022)
Instant shirataki noodles are included in functional foods made from iles-iles tubers (Amorphophallus onchopyllus). Instant shirataki noodles have several benefits because of the glucomannan content in iles-iles tubers. This product experienced a positive increase in demand despite limitations in terms of consumer segment and product availability. This shows that there is a possible purchase motivation by the belief that the product is safe and healthy compared to ordinary instant noodles. The purpose of this study was to analyze the factors that influence the purchase intention of consumers of instant shirataki noodles by expanding the Theory of Planned Behavior. This study used primary data obtained through an online questionnaire. The samples in this study were 450 people. Sample determination using the Purposive sampling method. Data analysis in this study used descriptive analysis and Partial Least Square (PLS-SEM). The results showed that E-TPB model proved to be better in explaining the effect of purchase intention on instant shirataki noodles with variables that had a positive and significant direct effect on intentions, namely attitudes towards behavior, subjective norms, perceived behavioral control, health awareness and perceived availability. In addition, the findings suggest that health awareness and perceived availability can have a significant indirect effect on intentions. The strategy is to create marketing events by inviting consumer reference groups, collaborating with social media influencers, providing customer testimonials, and increasing promotions and product availability.